PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS SCIENTIFIC APPROACH TERINTEGRASI NILAI KARAKTER UNTUK SISWA SEKOLAH DASAR DI YOGYAKARTA - - Suyantiningsih; Isniatun Munawaroh; Sisca Rahmadona (Universitas Negeri Yogyakarta, 2016)
DEVELOPING LEARNING MULTIMEDIA BASED SCIENTIFIC APPROACH INTEGRATED WITH CHARACTER VALUES FOR ELEMENTARY SCHOOL’S STUDENTS IN YOGYAKARTA This study was aimed at developing a learning multimedia based scientific approach integrated with character values for elementary students’ in Yogyakarta. The approach usedin this study was Research and Development (R D) which was adopted from development model of Borg and Gall. Subjects consisted of teachers and students at first grade in elementary school of Yogyakarta. Data was collected using questionnaire, observation, and documentation study, supported with focus group discussion (FGD) and also logbook.Data was analysed using through descriptive quantitative and qualitative. The results were including: (1) Based on preliminary research it can be found that character education has not been implemented effectively; (2) Focus Group Discussion (FGD) indicates that the integration of character education into subject matters is significant and a must; and (3) A prototipe of learning multimedia was developed and produced; and the multimedia had been validated by experts (media and material).